Speech with voice prosthesis after removal of the larynx – standard of speech therapy - Hamerlińska, Agnieszka (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
The text describes the treatment methods used in people with advanced larynx cancer. In the article has been described a voice prosthesis implanted after surgical removal of the larynx. The resulting speech is a tracheoesophageal fistula with insertion of vocal prosthesis. Tracheoesophageal fistula and esophageal speech were compared by analyzing the literature. The purpose of the text is to present the standard of speech therapy in patients after total laryngectomy, in whom the tracheoesophageal vocal prosthesis was implanted.